Education and language: A human right for sustainable development in Africa - Babaci-Wilhite, Zehlia; Geo-JaJa, Macleans A.; Lou, Shizhou (International review of education, 2012)
Pre-colonial Africa was neither an educationally nor a technologically unsophisticated continent. While education was an integral part of the culture, issues of language identification and standardisation which are subject to contentious debate today were insignificant. Children learned community knowledge and history by asking questions instead of being taught in a hegemonic alien language. This article argues that education and development should take place in a broader context of human rights, and explores the links between three areas often dealt with separately, namely: language, education and development. The authors of this paper demonstrate that changing the face of the multi-dimensionalities of poverty within societies is possible only when education is constructed in a rights perspective over the favoured colonial languages, which are not an integral part of the culture and resources of a community. The authors make a distinction between the right to education and rights in education, the latter of which are found to be more significant for the challenges Africa faces. It is argued here that the elements of Amartya Sen's "threshold" conditions for inclusion in human rights and self-development in education are essential, and that a more promising architecture of education would include what the authors term meta-narrative frameworks, i.e. interrelated policies. The authors contend that the neoliberal commodification of the knowledge sector has only exacerbated human rights and capabilities deprivation — which encompasses both human and income poverty. Éducation et langage : un droit fondamental en vue du développement durable en Afrique — L'Afrique précoloniale était un continent sophistiqué tant sur le plan éducatif que technologique. Si l'enseignement faisait partie intégrante de la culture, les questions d'identification et de standardisation linguistiques, aujourd'hui sujettes à des débats controversés, n'étaient pas significatives. Les enfants acquéraient le savoir et l'histoire de la communauté en posant des questions, et non pas en étant instruits dans une langue étrangère et hégémonique. Les auteurs avancent que l'éducation et le développement devraient avoir lieu dans le contexte élargi des droits fondamentaux, et examinent les liens entre trois domaines fréquemment traités isolément, à savoir : langage, éducation et développement. Ils démontrent qu'il n'est possible de changer la face multidimensionnelle de la pauvreté au sein des sociétés que si l'éducation est élaborée dans une perspective de droits fondamentaux primant sur les langues coloniales privilégiées, qui ne font pas partie intégrante de la culture et des richesses d'une communauté. Les auteurs font une distinction entre le droit à l'éducation et les droits dans l'éducation, ces derniers étant jugés plus importants pour répondre aux défis auxquels l'Afrique est confrontée. Les auteurs argumentent que les conditions « minimales » d'Amartya Sen devant être incluses dans les droits fondamentaux ainsi que le développement personnel dans l'éducation sont des éléments essentiels; en outre qu'une architecture de l'éducation plus prometteuse contiendrait ce que les auteurs appellent des cadres « méta-narratifs », c'est-à-dire des politiques étroitement liées. Ils affirment que la marchandisation néo-libérale du secteur des connaissances n'a fait qu'aggraver la privation des droits fondamentaux et des capacités — se traduisant par la pauvreté tant humaine que monétaire. Bildung und Sprache: Ein Menschenrecht für nachhaltige Entwicklung in Afrika — Weder technologisch noch im Hinblick auf Bildung war das präkoloniale Afrika primitiv. Bildung war ein integraler Bestandteil der Kultur, und Fragen nach sprachlicher Identität und Standardisierung, die heute zänkisch debattiert werden, waren schlicht bedeutungslos. Kinder erlernten das Wissen und die Geschichte der Gemeinschaft durch Erfragen, anstatt in einer hegemonialen, fremden Sprache unterrichtet zu werden. Die Autoren dieses Beitrags treten dafür ein, Bildung und Entwicklung in einem größeren Zusammenhang der Menschenrechte zu verorten. Sie erkunden dazu die Verbindungen zwischen drei Bereichen, die oft separat behandelt werden: Sprache, Bildung und Entwicklung. Der Beitrag zeigt, dass die vieldimensionalen Erscheinungsformen von Armut innerhalb von Gesellschaften nur dann im Kern verändert werden können, wenn Bildung aus einer Rechteperspektive über die bevorzugten Kolonialsprachen gestellt wird, denn diese Sprachen sind kein integraler Bestandteil der Kultur und der Mittel einer Gemeinschaft. Die Autoren unterscheiden zwischen dem Recht auf Bildung und Rechten in der Bildung, wobei sie Letztere im Hinblick auf die drängenden Probleme Afrikas für bedeutungsvoller halten. Grundlegend sind aus ihrer Sicht die von Amartya Sen formulierten „Schwellenbedingungen“für den Einschluss in die Menschenrechte und die Persönlichkeitsentwicklung in der Bildung. Ein aussichtsreicherer Ansatz für Bildung müsse untereinander verwobene politische Prozesse beinhalten, für die die Autoren den Begriff „meta-narrative Strukturen“vorschlagen. Die Autoren vertreten die These, dass die neoliberale Kommodifizierung des Wissenssektors den Entzug von Menschenrechten und Fähigkeiten beschleunigt und somit menschliche wie auch wirtschaftliche Armut verursacht. Educación y lengua: un derecho humano para el desarrollo sostenible en África — África nunca ha sido un continente con bajos niveles de exigencia en educación y tecnología durante su época precolonial. Dado que la educación era una parte integral de la cultura, no tenían relevancia los problemas de identificación y estandarización de la lengua que hoy provocan grandes controversias. Los niños adquirían conocimientos sobre la comunidad y la historia formulando preguntas, en lugar de ser instruidos en una lengua extranjera hegemónica. En este artículo se plantea que la educación y el desarrollo deberían tener lugar en un contexto amplificado de derechos humanos y se explora cómo están enlazadas tres áreas que frecuentemente se tratan por separado, a saber: lengua, educación y desarrollo. Los autores de este trabajo demuestran que cambiar la cara de las multidimensionalidades de la pobreza dentro de las sociedades solamente es posible cuando la educación se construye dentro de una perspectiva de derechos, por encima de las favorecidas lenguas coloniales que no son parte integrante de la cultura ni de la riqueza de una comunidad. Los autores establecen una distinción entre el derecho a la educación y los derechos en la educación, considerando que estos últimos tiene mayor relevancia para los retos que África está enfrentando. Argumentan que las "condiciones umbral" de Amartya Sen para la inclusión en derechos humanos y autodesarrollo en la educación son esenciales, y que una arquitectura de la educación más prometedora podría incluir lo que los autores denominan marcos "metanarrativos"; por ejemplo, políticas interrelacionadas. Los autores afirman que la mercantilización neoliberal del sector del conocimiento solamente ha empeorado la privación de derechos humanos y de capacidades, abarcando tanto la pobreza humana como la pobreza en función de los ingresos. Образование и язык: Права человека на устойчивое развитие в Африке — Преколониальная Африка не представляла собой образовательно или технологически неразвитый континент. В то время как образование являлось неотьемлемой частью культуры, проблемы языковой идентификации и стандартизации, которые являются сегодня предметом непрекращающихся дебатов, были незначительными. Дети постигали общественное знание и историю, задавая вопросы, вместо того, чтобы обучаться на господствующем чуждом языке. В данной статье приводятся аргументы в пользу того, что обучение и развитие должно происходить в более широком контексте прав человека. В ней исследуются взаимосвязи между тремя сферами, часто рассматриваемыми по отдельности, а именно, между языком, образованием и развитием. Авторы демонстрируют, что изменение многостороннего лица бедности в обществах возможно только при условии, что концепции обучения разрабатываются с позиций прав человека, а не привилегированных колониальных языков, которые не являются составной частью культуры и ресурсов сообществ. Авторы проводят различие между правот на обучение и правати в обучении, последние из которых являются более значимыми с точки зрения стоящих перед Африкой проблем. В статье обосновывается, что элементы пороговых условий Амартии Сена по приобщению к правам человека и саморазвитию в образовании являются обязательными, и что более благоприятная архитектура образования должна включать то, что авторы разывают «метанарративными» структурами, то есть взаимосвязанные политики. Авторы заявляют, что неолиберальная коммодификация сектора знаний привела лишь к усугублению процесса утраты прав и возможностей человека — что включает как личностное, так и финансовое обеднение.